DESCRIPCIÓN DE FÓSILES PROCEDENTES DE UNA PERFORACIÓN EFECTUADA EN LA PROVINCIA DE SANTA CRUZ (ARGENTINA) (Ameghiniana, 2013)
In the present paper some fossíls found in borings made in Santa Cruz Province are described. The marine fauna is composed maínly of Foraminífera, Cephalopoda, Gastropoda and Pelecypoda, of which only the better preserved Mollusca are consídered. The following taxa are described: Ineeeramus lateris n. sp., Pholadomya leanzai n. sp., Turritella donarium. n. sp. and Eubaculites sp. The age of the section in which these Iossils were found ranges Irom the Upper Cretaceous (Maestrichtian) to the Tertiary (Eocene).